Madrasah Head Management In Improving Character Education Through Skills Day Activities - Wiyono; Zakariyah (Journal of Social Science and Economics, 2022)
The application of character education in madrasas is a must to build the personality of a student. However, the reality in the field sometimes experiences obstacles so that there are gaps. This encourages MA NU Sunan Giri Talang Prigen, Pasuruan Regency to strive to realize the implementation of character education for students through Skills Day activities to be more optimal. In this regard, further discussion is needed regarding the management of madrasah principals in improving character education through Skills Day activities in MA. NU Sunan Giri Talang Prigen Pasuruan Regency. This research was carried out with the aim of describing several things which include (1) Planning for Character Education through Skills Day Activities in MA. NU Sunan Giri Talang Prigen Pasuruan Regency, (2) Implementation of Character Education through Skills Day Activities at MA NU Sunan Giri Talang Prigen Pasuruan Regency, (3) Results of Character education through Skills Day activities at MA NU Sunan Giri Talang Watuagung Prigen This research uses a phenomenological qualitative approach and a descriptive qualitative research type. Data were obtained through observation, interviews, and documentation. The research subjects were principals, teachers, and supervisors. Data analysis activities start from the data reduction stage, display data (data presentation), then draw conclusions/verification. Checking the validity of the data is carried out by diligent observation and triangulation. Based on the research, the following results were obtained: First, the management of madrasah principals in improving character education through Skills Day activities at MA NU Sunan Giri Talang Prigen Pasuruan Regency including (1) collaborating with various parties both from within the madrasa and from outside the madrasa, (2 ) adding hours of implementation outside of effective hours, (3) recruiting coaches from outside the madrasa who are competent, and (4) madrasas make interesting activities to motivate student participation. Second, the implementation of character education through "Skills Day" activities begins with religious activities, followed by extracurricular activities and the last is LSBM (Madrasah-Based Lesson Study) educational activities which are carried out routinely every Friday.